Prevalence and Comorbidity of Adult Attention Deficit and Hyperactivity Disorder Among the Patients Applying to Kocaeli University’s Psychiatry Polyclinic - Başak Küçük; Buket Özkara Yilmaz (Baiman Bauntung Batuah Center, 2022)
The present study aimed to determine the prevalence of ADHD diagnosis among the patients applying to adult psychiatry polyclinic for the first time and to determine comorbid diseases among the patients diagnosed with ADHD. The present study was carried out on patients who applied to the Psychiatry Polyclinic in the Medical Faculty Hospital of Kocaeli University Turkey between 10.01.2018 and 03.01.2019, with 151 patients involved in this study. After providing the participating patients with a verbal and written briefing about the study, the Sociodemographic Information Form and AADHDS were given to the participants. DIVA2.0 Adult ADHD Diagnostic Interview Scale and SCID-1 were implemented. As found in DIVA 2.0 ADHD Diagnostic Interview Form for Adults, 19.9% of 151 patients were diagnosed with adult ADHD, and 80.1% were not. Given SCID-1 diagnoses of patients, it was determined that, of the patients diagnosed with ADHD, 16.6% were diagnosed with depression, followed by generalized anxiety disorder (10%), and panic disorder and depression (10%), and that 13.3% of participants were not diagnosed with another disorder. Participants diagnosed with ADHD were found to have lower mean age. Prevalence of ADHD diagnosis was found to be lower among singles and students. The individuals diagnosed with ADHD were found to have a more prolonged education period. The prevalence of ADHD was higher among those who received a disciplinary punishment. Making an accurate diagnosis, designing an appropriate treatment, and determining the comorbidities of ADHD and with which psychiatric disorders it is confused would positively contribute to outcomes of treatments and increase the patients’ quality of life.